Quadratic Equations By Completing the Square Download Quadratic Equations By Completing the Square.pdf (23.9 KB) Page \( \langle 1\rangle \) of 2 9) \( r^{2}-4 r-91=7 \) 11) \( k^{2}-4 k+1=-5 \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To solve the equation \( r^{2}-4 r-91=7 \), start by rearranging it to standard form: \( r^{2}-4 r-98=0 \). Next, to complete the square, take half of the coefficient of \( r \) (which is -4), square it to get 4, and add/subtract this within the equation. This gives us \( (r-2)^2 - 4 - 98 = 0 \). Solve for \( r \) to find the roots. For the equation \( k^{2}-4 k+1=-5 \), similarly, rearrange it into standard form: \( k^{2}-4 k+6=0 \). Completing the square here, take half of -4 (that's -2), square it to reach 4 and adjust the equation to \( (k-2)^2 - 4 + 6 = 0 \). Solve for \( k \) to uncover the solutions. Happy calculating!